ANTAGONISM TESTING ON AN ETHANOL EXTRACT PREPARATION OF YELLOW ROOT STICKS (Arcangelisia flava L. Merr) TOWARD Yersinia enterocolitica AND Salmonella typhi BACTERIA - Hujjatusnaini, Noor; Amin, Astuti Muh; Widyadana, Rafif Ibnu; Annisa, Nur; Mila, Nor; AÃn, Latifah Nur (Jurnal Pendidikan Matematika dan IPA, 2024)
Yellow root (Arcangelisia flava L. Merr) contains ethanol compounds which is able to inhibit bacterial growth, both gram negative bacteria such as Stapylococcus aureus, Shigella sp., and Escherichia coli, as well as gram positive bacteria such as Yersinia enterocolitica, Streptococcus, Salmonella typhi, and Clostridium. This research is an experimental research that aims to determine the nature of antagonism (adaptability) between Yersinia enterocolitica bacteria and Salmonella typhi bacteria by administering yellow root extract at concentrations of 30%, 40%, 50%, and 60% within 24 hours, 48 hours, and 72 hours. The results showed that the positive control and negative control treatmens were not able to inhibit the growth of Yersinia enterocolitica bacteria and Salmonella typhi bacteria.Yellow root extract has acidity that effectively inhibits Yersinia enterocolitica bacteria at a concentration of 50%, while the most effective concentration for inhibiting the growth of Salmonella typhi bacteria is a concentration of 30%. Besides that, there are also differences in adaptability between Yersinia enterocolitica bacteria and Salmonella typhi bacteria. Salmonella typhi bacteria is more adaptable then Yersinia enterocolitica bacteria, this is evidenced by the inhibition zone formed which is smaller than Yersinia enterocolitica bacteria.